Peran Brand Image Situs Tripadvisor Memediasi Pengaruh Ewom terhadap Niat Beli Kamar di Kabupaten Badung - Citra Dewi, Putu Putri; Utama, I Putu; Widawati, Ida Ayu Putri (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2022)
EWOM given by other consumers in a sharing review platform or community can influence consumers' purchase intentions. TripAdvisor as an online review site that provides access for its customers to write a review. On the TripAdvisor site, people who want to share their experiences are required to become regular users and have their TripAdvisor account first and it is known that 65% of respondents see hotel reviews before making a booking. Thus, high ratings and good reviews from customers can create profits for hoteliers as EWOM can help hotels attract new customers. The purpose of this study was to determine the effect of EWOM on room purchase intention in Badung Regency and the role of Tripadvisor website brand image in mediating the relationship between EWOM and room purchase intention. This research method uses a quantitative approach and Partial Least Square Structural Equation Modeling (PLS-SEM) analysis. The population determined in this study is the Indonesian population with a sample of 180 respondents in accordance with the provisions of the sample calculation. The equation models analyzed are the outer model, the inner model and hypothesis testing. Based on the results of calculations using PLS-SEM software, the results show that there is no significant effect between the effect of EWOM on room purchase intentions, there is a significant effect of brand image on EWOM, the brand image of the Tripadvisor site has an effect on room purchase intention and there is a significant influence on brand image the Tripadvisor website as a media to mediate the influence of EWOM on room purchase intentions in Badung Regency. The implication of the results of this study shows that hotels around Badung Regency must maintain professionalism in improving the quality of services and facilities provided to tourists so that they can increase the value of reviews on the Tripadvisor site.